The health systems of the Kingdom of Bhutan and the development of a nationwide distance in-service training system for health human resources using ICT - Kozo, Watanabe (Kokusai Hoken Iryo (Journal of International Health), 2023)
Introduction  In-service training is an incentive to work and improve the quality of services of health human resources. In-service training for health human resources requires multi-sectoral efforts across relevant institutions, including the Ministry of Health (MOH), which is responsible for policy, and higher education institutions, teaching hospitals, etc.  The only national medical university of Bhutan, KGUMSB has developed a nationwide distance in-service training system using ICT, which had been prepared during the COVID-19 pandemic. Prior studies have reported that there are benefits to the use of ICT for in-service training in low- and middle-income countries to compensate for resource shortages.  In January 2023, a Memorandum of Understanding (MOU) was signed between the MOH and KGUMSB, etc. to cooperate and collaborate in the in-service training of health human resources across Bhutan.  This paper provides an overview of Bhutanese health systems and introduces how to establish a nationwide in-service training system by connecting central and regional health institutions through distance education using ICT, in the case of Bhutan.Methods  Participant observation, online interviews with stakeholders from KGUMSB, MOH, JICA, and documentary researches were conducted till July 2023.Results  ICT environment and simulation training center at KGUMSB and two regional referral hospitals (teaching hospitals) developed. KGUMSB developed facilities and systems for distance education (digital education equipment, learning management system, etc.), training of trainers, and distance education content. In addition, the MOU for in-service training was signed between the MOH, KGUMSB, etc.Conclusion  Through the efforts of KGUMSB, a specialized institution for health human resource development in Bhutan, to develop a distance education system, the MOU was concluded with MOH, and a nationwide in-service training system for health human resources was formed. For this system to work, in low- and middle-income countries with limited resources, a collaboration between the MOH, medical university, and teaching hospitals is essential.